2021
DOI: 10.1126/sciadv.abd1705
|View full text |Cite
|
Sign up to set email alerts
|

Nonreplicable publications are cited more than replicable ones

Abstract: We use publicly available data to show that published papers in top psychology, economics, and general interest journals that fail to replicate are cited more than those that replicate. This difference in citation does not change after the publication of the failure to replicate. Only 12% of postreplication citations of nonreplicable findings acknowledge the replication failure. Existing evidence also shows that experts predict well which papers will be replicated. Given this prediction, why are nonreplicable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 31 publications
8
53
0
1
Order By: Relevance
“…Oppositely, the CPT, despite still being far from clinical pain, has a longer duration and reaches higher intensity (i.e., maximum tolerance), leading to a sensation that is a better proxy to real-life pain ( 20 , 21 ). In addition, given the ongoing “replication crisis” affecting natural sciences ( 52 , 53 ), the successful replication of our previous results on a different type of experimentally induced pain adds value to the current study.…”
Section: Discussionsupporting
confidence: 54%
“…Oppositely, the CPT, despite still being far from clinical pain, has a longer duration and reaches higher intensity (i.e., maximum tolerance), leading to a sensation that is a better proxy to real-life pain ( 20 , 21 ). In addition, given the ongoing “replication crisis” affecting natural sciences ( 52 , 53 ), the successful replication of our previous results on a different type of experimentally induced pain adds value to the current study.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, overestimation of expected utility gain can happen if research which we are more certain will not replicate tends to get cited more often. Recent research indicates the latter situation might often be the case (Serra-Garcia & Gneezy, 2021). Note that we could in principle repeat this thought experiment for any two variables in figure 4 not already joined by a causal arrow.…”
Section: Discussionmentioning
confidence: 76%
“…This problem is escalated by the policies of top journals and many grant institutions, which always favor the use of the newest technology to answer a research question. An indication that method hopping contributes to replication failures is the fact that publications in high-profile journals such as Nature and Science that could not be replicated are cited 153 times more often than those studies that could be successfully replicated ( Serra-Garcia and Gneezy, 2021 ). It is suggested that more-cited papers have more “interesting” results driven by new technologies which leads to a subjectively more lax peer-review process and subsequently to a negative correlation between replicability and citation count ( Serra-Garcia and Gneezy, 2021 ).…”
Section: A Summary Of Reasons That Contribute To Replication Failures...mentioning
confidence: 99%